1995
DOI: 10.1006/viro.1995.0008
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Conserved Domain I of the Sendai Virus L Polymerase Protein Uncouple Transcription and Replication

Abstract: To begin to map functional domains of the Sendai P-L RNA polymerase complex we wanted to characterize the P binding site on the Sendai L protein. Analysis of in vitro and in vivo P-L polymerase complex formation with carboxyl-truncations of the L protein showed that the N-terminal half of the protein was required. Site-directed mutagenesis of the Sendai virus L gene was employed to change amino acids within a highly conserved region of the N-terminal domain I from amino acids (aa) 348-379 singly or in pairs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
51
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 0 publications
4
51
1
Order By: Relevance
“…For Sendai virus (SeV), CRI is implicated in recruitment of N protein during replication and interaction with P protein (8) and CRII appears to play a role in template binding (27,38). Whether these regions of L mediate the same function in VSV has not been determined.…”
mentioning
confidence: 99%
“…For Sendai virus (SeV), CRI is implicated in recruitment of N protein during replication and interaction with P protein (8) and CRII appears to play a role in template binding (27,38). Whether these regions of L mediate the same function in VSV has not been determined.…”
mentioning
confidence: 99%
“…Alignment of the L proteins of viruses of the order Mononegevirales showed six domains of relatively high conservation, designated I to VI from the N terminus to the C terminus of the protein, which were proposed to specify the essential activities common to all L proteins (14, 15). Recent characterization of Sendai virus L mutants in each of the six domains suggests that multiple domains contribute to the different steps in viral RNA synthesis, since mutants in different domains gave the same defective phenotypes (2,3,7,11,16). Viral RNA synthesis is downregulated by the C proteins encoded from the P gene (12).…”
mentioning
confidence: 99%
“…The L proteins of paramyxoviruses are all over 2,000 aa, and studies to begin mapping the P binding site on L showed a general location in the N-terminal quarter or half of the protein (2,10,13). Of the mutants characterized in the various domains in the N-terminal half of Sendai virus L only one, S368R in domain I, abolished binding to Sendai virus P (2,7,16).…”
mentioning
confidence: 99%
“…They were either neutral, or inhibited or enhanced the polymerase function, or inhibited transcription without altering replication. Similarly, by mimicking the measles virus L protein around the conserved GHP motif of block I (position 372) (Chandrika et al, 1995), it was hoped to give the Sendai virus L protein the ability to bind the measles virus P protein (Horikami et al, 1994). However, uncoupling between transcription and replication was obtained.…”
mentioning
confidence: 99%